2013
DOI: 10.1182/blood-2013-07-514497
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated and unique functions of the E-selectin ligand ESL-1 during inflammatory and hematopoietic recruitment in mice

Abstract: • ESL-1 and PSGL-1 cooperate to mediate E-selectin binding, myeloid homeostasis, and inflammatory cell recruitment.• ESL-1 dominates E-selectin binding and homing of hematopoietic progenitors.Beyond its well-established roles in mediating leukocyte rolling, E-selectin is emerging as a multifunctional receptor capable of inducing integrin activation in neutrophils, and of regulating various biological processes in hematopoietic precursors. Although these effects suggest important homeostatic contributions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Although we identified PSGL-1 as the dominant functional P-selectin ligand on Tregs, consistent with observations in other leukocyte subsets (55,56), identifying the functional E-selectin ligands on Tregs is likely to be more challenging. Several leukocyte-expressed E-selectin ligands, including PSGL-1, E-selectin ligand-1, CD44, and CD43, have been identified (9,30,(56)(57)(58). Expression of E-selectin ligand-1 has not been reported on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although we identified PSGL-1 as the dominant functional P-selectin ligand on Tregs, consistent with observations in other leukocyte subsets (55,56), identifying the functional E-selectin ligands on Tregs is likely to be more challenging. Several leukocyte-expressed E-selectin ligands, including PSGL-1, E-selectin ligand-1, CD44, and CD43, have been identified (9,30,(56)(57)(58). Expression of E-selectin ligand-1 has not been reported on lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The PNEE acts in a manner similar to Yi-Qi-Fu-Sheng, a Chinese herbal formula, and Ganoderma lucidum, a traditional Chinese medicinal mushroom; all of these agents exhibit a concentration-dependent inhibitory effect on HCT-116 cell invasion and migration by decreasing wound healing ability and MMP-2 and/or MMP-9 activity (Chen et al, 2010;Deng et al, 2013). With the exception of the regulation of cell-cell interactions in the surrounding ECM and stromal substrate through decreases in MMP expression, the regulation of the permeability of cell-cell contact junctions and of the expression of junction proteins constitutes an important mechanism for suppressing migration and decreasing the invasion potential (Barthel et al, 2013;Sreeramkumar et al, 2013). In cell-cell contact structures, gap junctions, tight junctions, adherens junctions and desmosomes are distinct major intercellular structures that allow communication between neighboring cells and that maintain the integrity of the monolayer (Martínez-Palomo, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ICAM-1 can enhance immune cell adhesion and migration (49). These integrins mediate strong adhesion between cancer cells and endothelial cells (50), and this process promotes the transmigration of cancer cells through the endothelium to metastatic sites (51,52). Our previous study showed that P. notoginseng exerts anti-metastasis effects in HCT-116 cells by decreasing adhesion activity through reduction in the levels of such adhesion molecules, including integrin-1, E-selectin and ICAM-1 (9).…”
Section: Discussionmentioning
confidence: 99%